Re-making, Re-marking, or Re-using? Hermeneutical Strategies and Challenges in the Guhyasamaja Commentarial Literature - Hackett, Paul G. (Buddhist Studies Review, 2017)
This paper presents a case study in the exegesis of Buddhist tantric literature by examining a segment of the corpus of Guhyasamaja literature and, in doing so, addresses both emic and etic approaches to the hermeneutics of tantric texts. On the most basic level, we discuss the mechanisms for interpreting statements within the root tantra internal to the exegetical tantric literature itself, as exemplified by Candrakirti’s ‘Brightening Lamp’ (Pradipoddyotana) commentary and the extensive sub-commentary by Bhavyakirti. On another level, however, these same exegetical moves can be viewed in terms of the ideas ‘re-use’ and reformulation of the root text, and how they shape the understanding of the role and function of tantric commentary.